PERBANDINGAN HASIL PENGOMPOSAN MENGGUNAKAN METODE BATA TERAWANG DAN METODE OPEN WINDROW - Ilham; Sri Sumiyati; Sudarno (Postgraduate, University of Mataram, 2025)
Composting is a waste management process that converts organic material into humus that can be reused. Composting can be applied using several methods such as the open windrow method, this method is a way of making compost that will get sufficient aeration so that it will help the compost maturity process more quickly. The aim of this research is to compare the results of composting using the open brick method and open windrow based on chemical parameters. During the composting process, a different bioactivator was added to each compost, using two bioactivators, namely MoL and M-Bio, and periodic checks were carried out every three days during the six weeks of composting. Based on the comparison results, the C, P content and C/N ratio in the two methods produced content values ​​that were not significantly different, however, in the overlay brick method, the control compost was superior in terms of P content and C/N ratio. Meanwhile, the open windrow method has a consistent increase in C, P content and C/N ratio.